Renal blood flow detection with Doppler ultrasonography in patients with hepatic cirrhosis - Celebi, H; Donder, E; Celiker, H (Amer Medical Assoc, 1997)
Background: Hepatorenal syndrome, a well-recognized complication of established liver disease, is characterized by early renal vasoconstriction before clinically recognized renal disease. Renal vasoconstriction causes increased renal vascular resistance, which can be detected noninvasively by Doppler ultrasonography. Objective: To detect early renal hemodynamic changes in patients with hepatic cirrhosis who had clinically normal renal functions. Patients: Twenty patients with hepatic cirrhosis and ascites, 11 patients with hepatic cirrhosis without ascites, and 23 healthy control subjects. All cirrhotic patients had normal serum urea nitrogen and creatinine values. Main Outcome Measures: Peak systolic, peak diastolic, and mean flow velocities; pulsatile index; resistive index; and peak systolic velocity/peak diastolic velocity ratio as measured by renal Doppler ultrasonography. Results: Peak diastolic flow velocity was significantly lower in cirrhotic patients with ascites than in cirrhotic patients without ascites and control subjects (P<.02 and P<.004, respectively),but the peak systolic flow velocity/peak diastolic flow velocity ratio (P<.007 and P<.001, respectively), pulsatile index (P<.007 and P<.001, respectively), and resistive index (P<.007 and P<.001, respectively) were significantly higher in cirrhotic patients with ascites than in cirrhotic patients without ascites and controls. Conclusion: Renal Doppler ultrasonography can noninvasively identify a subgroup of nonazotemic patients with hepatic cirrhosis who are at high risk for subsequent development of renal dysfunction and hepatorenal syndrome.
Keywords: Failure; Kidney; Us